"Isolated" DyO+ Embedded in a Ceramic Apatite Matrix Featuring Single‐Molecule Magnet Behavior with a High Energy Barrier for Magnetization Relaxation. (18th September 2017) - Kazin, Pavel E.; Zykin, Mikhail A.; Utochnikova, Valentina V.; Magdysyuk, Oxana V.; Vasiliev, Alexander V.; Zubavichus, Yan V.; Schnelle, Walter; Felser, Claudia; Jansen, Martin
Abstract: Meeting the challenges of Moore's Law, predicting ambitious miniaturization rates of integrated circuits, requires to go beyond the traditional top‐down approaches, and to employ synthetic chemistry methods, to use bottom‐up techniques. During the recent decades, it has been shown that open‐shell coordination compounds may exhibit intramolecular spontaneous magnetization, thus offering promising prospects for storage and processing of digital information. Against this background we regarded it rewarding to implement similar magnetic centers into a ceramic material, which would provide better long‐term mechanical and chemical durability. Here we present new robust inorganic compounds containing separate DyO + ions in an apatite matrix, which behave like single‐molecule magnets. The materials exhibit a blocking temperature of 11 K and an energy barrier for spin reversal of a thousand inverse centimeters which is among the highest values ever achieved.